Severity and Selectivity of the Black Death and Recurring Plague in the Southern Netherlands (1349-1450) - Roosen, Joris (TSEG - The Low Countries Journal of Social and Economic History, 2018)
The Black Death is the textbook villain when it comes to the study of historical diseases and to the general public it remains a thought-provoking subject. To illustrate, in 2016 almost three million viewers accessed the English Wikipedia’s Black Death page, compared to present-day Ebola which only had around one million. Despite the wide drawing power of the Black Death, some of its most basic characteristics are still debated in academic circles. The focus of this paper will be on the severity of the Black Death and recurring plague outbreaks in the Southern Netherlands. More specifically it will reflect on the general assumption that plague evolved from a ‘universal killer’ to a more selective and less severe disease over time. Due to the scarcity of late medieval sources and a lack of quantifiable indicators, little is known about the causal mechanisms at work during the late Middle Ages. This paper offers a newly-compiled database of 25.610 individuals that died between 1349-1450 in the County of Hainaut to test a number of assumptions on the selectivity and severity of late medieval plague outbreaks.